2013
DOI: 10.3233/jad-130173
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrohyperforin Induces Mitochondrial Dynamics and Prevents Mitochondrial Ca2+ Overload after Aβ and Aβ-AChE Complex Challenge in Rat Hippocampal Neurons

Abstract: St. John's wort has been the subject of studies focused on its therapeutic properties against several diseases, including Alzheimer's disease (AD). Amyloid β-peptide (Aβ), a critical peptide in AD, has been linked to the mitochondrial dysfunction often observed in this disease. Despite many efforts to prevent Aβ levels from increasing in AD, less has been done regarding the mitochondrial component. Therefore, we studied the effects of tetrahydrohyperforin (THH) on mitochondrial dysfunction of hippocampal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…N‐TYR is a marker of the oxidation of proteins generated by an increase in the production of nitric oxide (NO); we used a polyclonal antibody for detection (AbD Serotec, Oxford, UK). Our protocol has previously been described by our laboratory .…”
Section: Methodsmentioning
confidence: 99%
“…N‐TYR is a marker of the oxidation of proteins generated by an increase in the production of nitric oxide (NO); we used a polyclonal antibody for detection (AbD Serotec, Oxford, UK). Our protocol has previously been described by our laboratory .…”
Section: Methodsmentioning
confidence: 99%
“…This phytochemical is found in St. John’s wort ( Hypericum perforatum ), which has been considered herbal medicine since the ancient Greeks (Klemow et al, 2011) and is apparently helpful as antidepressant, antibacterial, antiviral, antineoplastic, anti-inflammatory, antioxidant, and neuroprotective (Dinamarca et al, 2006; Griffith et al, 2010). As a further AD-related benefit, the compound induces mitochondrial dynamics and prevents mitochondrial Ca 2+ overload after Aβ and Aβ–AChE complex challenge in rat hippocampal neurons (Zolezzi et al, 2013). Cheng et al (2013) show that nicotinamide mononucleotide adenylyltransferase 2 affects tau phosphorylation by regulating the activity of protein phosphatase PP2A, and suggest that this enzyme may serve as a potential target in arresting AD-like tau pathologies.…”
Section: Multiple Ways Of “Curing” Animal Ad Modelsmentioning
confidence: 99%
“…Our laboratory and others, have been working with PPARs for many years, and we have systematically described the benefits of PPARs activation in several in vitro and in vivo models of AD (Fuentealba et al, 2004; Inestrosa et al, 2005, 2012; Fuenzalida et al, 2007; Nenov et al, 2014). Moreover, recent works suggest an interesting role for PPARs in mitochondrial dysfunction protection and functionality (Zolezzi et al, 2013a,b), which could be part of a series of PPAR-triggered mechanisms at the foundation of the benefits observed against AD.…”
Section: Nuclear Receptors (Nrs): Ppars and Their Potential Role In Amentioning
confidence: 99%
“…Recently, it has been demonstrated that PPARs are able to protect endothelial cells from oxidative damage, thus preventing vascular dysfunction, which could favor brain parenchyma alterations (d’Uscio et al, 2012; Papadopoulos et al, 2013). Based on current knowledge and on our own work, we have proposed that PPAR activation, through natural or synthetic ligands, could protect and recover BBB integrity and functionality by increasing cell antioxidant capacity and improving energy metabolism, leading to the increased expression of specific transporters that could influence the Aβ-clearance rate (Nicolakakis et al, 2008; Zolezzi and Inestrosa, 2013; Zolezzi et al, 2013b; Hawkes et al, 2014). Energy metabolism is vital for both, neurons and the BBB, primarily because the preservation of the ion gradients (in the case of neurons) and the traffic across the BBB requires large amounts of energy (Abbott et al, 2010; Liebner and Plate, 2010; Popa-Wagner et al, 2013).…”
Section: Nuclear Receptors (Nrs): Ppars and Their Potential Role In Amentioning
confidence: 99%